МӘМЛЕКЕТИМИЗ ЭКОНОМИКАСЫНЫҢ СТРУКТУРАЛЫҚ ӨЗГЕРИСЛЕРИНИҢ ЖЕТИСКЕНЛИКЛЕРИ - Хожалепесов, П.; Ибрагимова, Г. (FAN va JAMIYAT, 2016)
The article presents the results of the reforms for the years of independence. It identifies the periods of economic modernization in the republic, the development of economy has been analyzed on the basis of statistical data. The author studies the issues of diversification of production and importance of investing in the economy.